2018
DOI: 10.3758/s13423-018-1503-0
|View full text |Cite
|
Sign up to set email alerts
|

Shared or separated representations for letters with diacritics?

Abstract: Understanding the front end of visual word recognition requires us to identify the processes by which letters are identified. Since most of the work on letter recognition has been conducted in English, letter perception modeling has been limited to the 26 letters of the Latin alphabet. However, many writing systems include letters with diacritic marks. In the present study, we examined whether diacritic letters are a mere variant of their base letter, and thus share the same abstract representation, or whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
64
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(78 citation statements)
references
References 16 publications
5
64
2
1
Order By: Relevance
“…Results showed that, for MONEDA-type words, the visually similar prime moñeda was not more effective than the visually dissimilar prime moseda (567 vs. 568 ms, respectively; i.e., there was no visual similarity effect); furthermore, the visually similar prime moñeda was less effective than the identity prime moneda (567 vs. 548 ms, respectively). This pattern (i.e., SIM = DIS; ID < SIM) extends not only the findings of Perea et al (2016Perea et al ( , 2018 in the Arabic script to the Latin script but also the findings of Chetail and Boursain (2019) and Domínguez and Cuetos (2018) from vowels to consonants in the Latin script. Nevertheless, the pattern of findings was different for MUÑECA-type words.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Results showed that, for MONEDA-type words, the visually similar prime moñeda was not more effective than the visually dissimilar prime moseda (567 vs. 568 ms, respectively; i.e., there was no visual similarity effect); furthermore, the visually similar prime moñeda was less effective than the identity prime moneda (567 vs. 548 ms, respectively). This pattern (i.e., SIM = DIS; ID < SIM) extends not only the findings of Perea et al (2016Perea et al ( , 2018 in the Arabic script to the Latin script but also the findings of Chetail and Boursain (2019) and Domínguez and Cuetos (2018) from vowels to consonants in the Latin script. Nevertheless, the pattern of findings was different for MUÑECA-type words.…”
Section: Discussionsupporting
confidence: 81%
“…The present data also allow us to reinterpret the findings from Perea et al (2016Perea et al ( , 2018 is not due to the singular role of diacritical s igns in Arabic script, as Perea et al (2016Perea et al ( , 2018 proposed. A more parsimonious explanation is that the lack of visual similarity effects with primes containing letters with diacritical signs is a more general phenomenon: it occurs not only in Arabic but also in the Latin-based orthographies with accented vowels (tâper-TAPER = tuper-TAPER; Chetail & Boursain, 2019;Domínguez & Cuetos, 2018) and with consonant letters (moñeda-MONEDA = moseda-MONEDA), as in the current experiment.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations